لغة الخطاب الصوفي بين القراءة والتأويل (قراءة في بعض النماذج الشعرية - معمري, فواز (قــــــراءات, 2019)
يهدف هذا المقال إلى الكشف عن ما تحمله لغة الخطاب الصوفي  من دلالات وعلامات أيقونية  يمكنها المساهمة في عملية التواصل بين القارئ والنص، وكذا كشف أنماط الرمز الصوفي، وما يتولد عنه من قيم فنية، تسهم في تحديد الأسس والأبعاد الجمالية للخطاب الصوفي. وقد كانت خطوات البحث كالآتي: في البداية نحاول تقديم مفهوم الصوفية لغة واصطلاحا، ثم الحديث عن لغة الخطاب الصوفي، ولغة الخطاب الأدبي والفرق بينهما، لنخلص في الأخير إلى اللغة التي يستعملها ويلجأ إليها الصوفي من أجل خدمة أشعاره. الكلمات المفتاحية : الخطاب، الرمز، إشارة، بنية، سياق. Abstract This article aims to reveal sense of the language of the mystic (sufi) speech and its  connotations and iconic signs that can contribute to the process of communication between the reader and the text, as well as the to reveal the mystic symbol styles, and what generated about it as artistic values  which contribute to determinate fundamentals and aesthetic dimensions of mystic speech. Research steps were as follows: At first we trying to present the Sufi concept (language and idiomatically), and then talking about the language of the mystic speech, the language of literary speech and the difference between them, to summarize in the final to the language used by the sufi and that he resorted to in order to serve his texts and poems   Key words : DISCOURS – ICON – SIGN – STRUCTURE - GONTEXTE